Micro and nano plastics release from a single absorbable suture into simulated body fluid - Boland, John; Xiao, Liwen (My University, 2024)
Synthetic polymers are widely used in medical devices and implants where biocompatibility and mechanical strength are key enablers of emerging technologies. One concern that has not been widely studied is the potential of their microplastics (MPs) release. Here we studied the levels of MP debris released following 8-week in vitro tests on three typical polyglycolic acid (PGA) based absorbable sutures (PGA 100, PGA 90 and PGA 75) and two nonabsorbable sutures (polypropylene-PP and polyamide-PA) in simulated body fluid. The MP release levels ranked from PGA 100 > > PGA 90 > PGA 75 > > PP ~ PA. A typical PGA 100 suture released 0.63 ± 0.087 million micro (MPs > 1 µm) and 1.96 ± 0.04 million nano (NPs, 200–1000 nm) plastic particles per centimeter. In contrast, no MPs were released from the nonabsorbable sutures under the same conditions. PGA that was coblended with 10–25% L-lactide or epsilon-caprolactone resulted in a two orders of magnitude lower level of MP
PUBLISHED
cited By 0
Keywords: Synthetic polymers; polyglycolic acid (PGA); absorbable sutures